PENGARUH PEMBERIAN SUSU KEDELAI TERHADAP KADAR GLUKOSA DARAH PENDERITA DIABETUS MELITUS TIPE 2 - Febriyanto, Dicky Nurwahyu; Prihatin, Setyo (JURNAL RISET GIZI, 2016)
Background : Diabetus mellitus (DM) is a disease whose prevalence is increasing every year. Need to do the control, prevention, and to set DM 4 main pillars, there are dietary therapy, exercise, counseling, and treatment. The level of patient compliance in implementing diet and taking medication therapy DM is still low. Should look for functional foods in the management of Type 2 diabetic patients such as soy milk. Based on the nutrient content in the form of the amino acid arginine, lecithin, fiber and minerals chromium, soy milk is beneficial to increase insulin sensitivity and glucose metabolism blood that help blood glucose levels may be decreased. Objective : This study aimed to determine the effect of soy milk on blood glucose levels of patients DM type 2. Method : The design of this study was pretest - posttest control group design with a sample of 10 people in the treatment group and 10 people in the control group. The sample in this study is that patients in FKTP (Health Facility Level One) dr. Heru Setyono located in Blora district. Result : The results showed that administration of soy milk for 7 days can lower fasting blood glucose in the treatment group by 13.9 mg / dl. Statistical test results Paired T test (sig 0.005), indicating that there is difference between the blood glucose levels before and after treated by administration of soy milk for 7 days in the treatment group. Conclusion : It is concluded that the provision of as much as 25 grams of soy milk is given 2 times a day within 7 days, it can lower blood sugar levels as much as 13.9 mg / dl. It is advisable to be developed as an alternative therapy in patients by DM type 2.